Demand for Rental Housing: Evidence from Slum Settlements in Delhi. (May 2017) - Gupta, Manish; Gupta, Ruchita
Government policies have largely focussed on ownership-based models while addressing the challenge of low-income housing in urban India. Possibilities of rental housing, which is an important form of housing for the urban poor, have not been explored meaningfully. This article estimates the demand for rental housing and its attributes in Delhi's slums using primary survey data of tenant households. Estimates of demand for rental housing attributes reveal rent to be higher for dwellings that have a separate kitchen, bathroom, reasonably good access to water and wide approach roads. The results further show the demand for rental housing to be inelastic with respect to price (i.e., rent) and income. However, rent has a greater influence on housing consumption than income. Households prefer living closer to their workplace and value security of tenure. Policies aimed at moderating rents are likely to be more effective in enhancing housing consumption. The policy focus should be on improving infrastructure in the slums, their in situ redevelopment and ensuring security of tenure.